RETRACTED:Peran Perencanaan dalam Pembangunan Lembaga Pendidikan Islam Modern - Luthfie Noor Fithriasari; Muhammad Yahya Ashari (Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam, 2023)
Following a rigorous, carefully concerns and considered review of the article published in Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam, e-ISSN 2686-5289 to article entitled “Peran Perencanaan Dalam Pembangunan Lembaga Pendidikan Islam Modern” Volume 5, No 2, pp. 1-10, December 2023, DOI: https://doi.org/10.61181/ats-tsaqofi.v5i2.321 This paper has been found to be in violation of the Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam Publication principles and has been retracted. The article contained redundant material, the editor investigated and found that the paper published in At Tadbir: Islamic Education Management Journal, e-ISSN 3021-8098, Volume 1 Nomor 2, November 2023), pp. 84-97, https://doi.org/10.54437/attadbir.v1i2.1312, entitled "Peran Perencanaan Dalam Pembangunan Lembaga Pendidikan Islam Modern". The document and its content has been removed from Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam, and reasonable effort should be made to remove all references to this article.